2022
DOI: 10.1093/stcltm/szab030
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mesenchymal Stem Cell Spheroids with Enhanced Stem Cell Characteristics and Bone Regeneration Ability

Abstract: Mesenchymal stem cells (MSCs) exhibit self-renewal, multi-lineage differentiation potential and immunomodulatory properties, and are promising candidates for cellular therapy of various tissues. Despite the effective function of MSCs, the gradual loss of stem cell characteristics that occurs with repeated passages may significantly limit their therapeutic potential. A novel 3D shaking method was previously established to generate MSC spheroids in growth medium (GM-spheroids) and successfully maintain the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Stem cell multipotency has been reported to be restored by mechanical stimuli in 3D cultures. A previous study demonstrated that shaking culture restored the multipotency of mouse 22 and human MSC spheroids after long-term expansion ex vivo 23 . In an iPSC study, mechanical stimulation using equiaxial stretching enhanced reprogramming e ciency, but did not enhance the transduction rate 24 .…”
Section: Discussionmentioning
confidence: 95%
“…Stem cell multipotency has been reported to be restored by mechanical stimuli in 3D cultures. A previous study demonstrated that shaking culture restored the multipotency of mouse 22 and human MSC spheroids after long-term expansion ex vivo 23 . In an iPSC study, mechanical stimulation using equiaxial stretching enhanced reprogramming e ciency, but did not enhance the transduction rate 24 .…”
Section: Discussionmentioning
confidence: 95%
“…Stem cell multipotency has been reported to be restored by mechanical stimuli in 3D cultures. A previous study demonstrated that shaking culture restored the multipotency of mouse 19 and human MSC spheroids after long-term expansion ex vivo 20 . In an iPSC study, mechanical stimulation using equiaxial stretching enhanced reprogramming efficiency, but did not enhance the transduction rate 21 .…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to two-dimensional dedifferentiated fat cells, three-dimensional dedifferentiated fat spheroid promoted osteogenic differentiation and bone formation via canonical Smad 1/5 signaling pathways, according to research comparing the in vitro osteogenic potential of rat dedifferentiated fat cells cultured under osteogenic conditions in three-dimensional spheroids with that in two-dimensional monolayers [ 24 ]. The bone regeneration process was accelerated in vivo by neurosphere medium spheroids created under modified neurosphere culture conditions with constant shaking [ 25 ]. In contrast, constructions using two-dimensional and three-dimensional bone marrow mesenchymal stem cells behaved comparably in vivo despite a tendency for improved in vitro calcification [ 23 ].…”
Section: Discussionmentioning
confidence: 99%